The effect of bright light therapy in migraine patients with sleep disturbance: A prospective, observational cohort study protocol - Lin, Tsung-Hsing; Yang, Cheng-Chia; Lee, Shih-Yu; Chang, Ching-Mao; Tsai, I-Ju; Wei, Cheng-Yu; Yang, Chun-Pai (Frontiers in Aging Neuroscience, 2023)
Background. Migraine is a common disabling disorder, and its substantial burden is associated with a considerable negative impact on the patients’ quality of life. Moreover, aging patients with migraine have more cognitive complaints. Additionally, the elderly are more likely to have sleep disturbances, which may also predict the risk of incident dementia. Migraines are reported to be closely associated with sleep and circadian rhythms. Sleep disturbance is a well-known trigger for migraine episodes; moreover, shift work or jet lag reportedly triggers some migraines. The hypothalamus is thought to be the migraine generator; sleep and circadian activity rhythm are also controlled by the hypothalamus. Evidence suggests an influence of both sleep and circadian system on migraine. Previously, light therapy has been show to stabilize sleep architecture and further improve insomnia related to circadian rhythm disorders. However, the beneficial effect of light therapy on migraine with sleep disturbance has not yet been determined. We aim to explore the effects of light therapy for migraine combined with sleep disturbance. Methods and analysis. This project is a 2-year, randomized, double-blind, placebo-controlled clinical trial. The study design includes a 4-week monitoring period (baseline and pretest), a 4-week treatment period, and a posttest. The study participants will undergo assessments on headache frequency and severity and subjective and objective (wrist actigraphy and polysomnography) sleep disturbances, and quality of life and a series of blood tests for serum biomarkers. Discussion. This study will establish evidence-based alternative medicine for the preventive effect of bright light therapy in migraine patients with sleep disturbances. Moreover, our data will be useful to comprehend the biochemical mechanism of light therapy in migraine prevention. Trial registration. ClinicalTrials.gov (NCT04890691). Ethics approval and consent to participate. The study was approved by the Institutional Review Board of Kuang Tien General Hospital (KTGH21002). Keywords: migraine, light therapy, circadian rhythms, PSG, neuropeptides, wrist actigraph